Immunodominance of the VP4 neutralization protein of rotavirus in protective natural infections of young children. - Ward, R L (1993)
Natural infection by very similar strains of rotavirus during the 1988-1989 rotavirus season in Cincinnati, Ohio, provided complete protection of young children against subsequent rotavirus illnesses for a period of at least 2 years. Using this limited strain variability, we characterized the association between the titers of antibody to either the VP4 or the VP7 neutralization protein and protection against subsequent rotavirus disease. This was done by using reassortants that contained only one of the two rotavirus neutralization proteins of 89-12, a culture-adapted isolate representative of the protective rotavirus strains. The other neutralization protein in these reassortants was derived from a heterologous rotavirus (WC3 or EDIM) to which the infected subjects made little or no neutralizing antibody (titers, < or = 20). The geometric mean titer (GMT) of antibody to 89-12 in convalescent-phase sera from the 21 subjects analyzed was 2,323. The GMT of antibody to a reassortant (strain WC-4) that contained the VP7 protein of 89-12 and VP4 of WC3 was 387. In contrast, the GMT of antibody to a reassortant (strain EDIM-7) that contained the VP4 protein of 89-12 and the VP7 protein of EDIM was 1,078. Thus, the major neutralization response was directed against VP4 rather than VP7, a finding that has important implications for development of appropriate rotavirus vaccines.